2009
DOI: 10.1016/s0065-2660(09)68002-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Social Interactions

Abstract: Studies of social behavior generally focus on interactions between two or more individual animals. However, these interactions are not simply between whole animals, but also occur between molecules that were produced by the interacting individuals. Such “molecular social interactions” can both influence and be influenced by the organismal-level social interactions. We illustrate this by reviewing the roles played by seminal fluid proteins (Sfps) in molecular social interactions between males and females of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 208 publications
(338 reference statements)
0
38
0
Order By: Relevance
“…The proteins that accompany sperm into the female—once dismissed as simply a supportive medium for sperm—are now known to be potent modulators of female reproductive biology; in some cases, they even have effects on offspring (reviewed in Martan and Shepherd 1976; Chapman 2001; Gillott 2003; Kubli 2003; Poiani 2006; Sirot et al 2009; Avila et al 2011; Rodríguez-Martínez et al 2011; Ratto et al 2012; Bromfield et al 2014). Most SFPs are the products of secretory glands in the male reproductive tract; these include the prostate glands, epididymi, and seminal vesicles of mammals (Poiani 2006; Rodríguez-Martínez et al 2011) and the male accessory glands and ejaculatory ducts/bulb of arthropods (Gillott 2003).…”
Section: The Battlegroundmentioning
confidence: 99%
See 3 more Smart Citations
“…The proteins that accompany sperm into the female—once dismissed as simply a supportive medium for sperm—are now known to be potent modulators of female reproductive biology; in some cases, they even have effects on offspring (reviewed in Martan and Shepherd 1976; Chapman 2001; Gillott 2003; Kubli 2003; Poiani 2006; Sirot et al 2009; Avila et al 2011; Rodríguez-Martínez et al 2011; Ratto et al 2012; Bromfield et al 2014). Most SFPs are the products of secretory glands in the male reproductive tract; these include the prostate glands, epididymi, and seminal vesicles of mammals (Poiani 2006; Rodríguez-Martínez et al 2011) and the male accessory glands and ejaculatory ducts/bulb of arthropods (Gillott 2003).…”
Section: The Battlegroundmentioning
confidence: 99%
“…Females of many insect species show dramatic changes in postmating behavior (reviewed in Gillott 2003; Sirot et al 2009; Avila et al 2011). In some species, mated females do not remate, or they remate at very low levels.…”
Section: Do Sfps Contribute To Postmating Sexual Conflict?mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, direct examination of sperm localization in the female reproductive tract has revealed that a component of the mating stimulus that is neither sperm nor male accessory gland product is sufficient to cause physical displacement of sperm 21 , 36 . Finally, SFPs influence levels of sperm competition through their effects on sperm recruitment, retention and distribution among SSOs (described below, and reviewed in refs 8 , 9 , 130 …”
Section: Female Multiple Matingmentioning
confidence: 99%